General phenomenon of organisational innovation and innovation diffusion / Prof. Dr. Norlaila Md Zin, Assoc. Prof. Dr. Eley Suzana Kasim and Ida Haryanti Mohd Noor - Md Zin, Norlaila; Kasim, Eley Suzana; Mohd Noor, Ida Haryanti (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The innovative ability of an organisation is an invaluable asset as it may be key to the organization achieving greater success (Azeem et al., 2021). The most used and cited Diffusion of Innovation Theory is that expounded by Roger in his book, The Diffusion of Innovations, 1962, 1983, 1995, and 2003. This latest (fifth) edition has been improved from merely providing summaries on the general diffusion research to the inclusion of a broader base of diffusion research to encompass the diffusion of the Internet. Rogers (2003) discusses the changes in the contributions of various diffusion traditions and explains the diffusion of new communication technologies, enhanced understanding of diffusion networks, and the use of field experimentation. He defines diffusion as “the process by which an innovation is communicated through certain channels over time among members of a social system” (Rogers, 2003, p.11). In this regard, he cites four main elements in the diffusion of innovations: (1) innovation, (2) communication channels, (3) time, and (4) the social system (Rogers,1983).